Decoupling of recombinant protein production from Escherichia coli cell growth enhances functional expression of plant Leloir glycosyltransferases. Issue 6 (5th February 2019) - Lemmerer, Martin; Mairhofer, Juergen; Lepak, Alexander; Longus, Karin; Hahn, Rainer; Nidetzky, Bernd
Abstract: Sugar nucleotide‐dependent (Leloir) glycosyltransferases from plants are important catalysts for the glycosylation of small molecules and natural products. Limitations on their applicability for biocatalytic synthesis arise because of low protein expression (≤10 mg/L culture) in standard microbial hosts. Here, we showed two representative glycosyltransferases: sucrose synthase from soybean and UGT71A15 from apple. A synthetic biology‐based strategy of decoupling the enzyme expression from the Escherichia coli BL21(DE3) cell growth was effective in enhancing their individual (approximately fivefold) or combined (approximately twofold) production as correctly folded, biologically active proteins. The approach entails a synthetic host cell, which is able to shut down the production of host messenger RNA by inhibition of the E. coli RNA polymerase. Overexpression of the enzyme(s) of interest is induced by the orthogonal T7 RNA polymerase. Shutting down of the host RNA polymerase is achieved by l ‐arabinose‐inducible expression of the T7 phage‐derived Gp2 protein from a genome‐integrated site. The glycosyltransferase genes are encoded on conventional pET‐based expression plasmids that allow T7 RNA polymerase‐driven inducible expression by isopropyl‐β‐ d ‐galactoside. Laboratory batch and scaled‐up (20 L) fed‐batch bioreactor cultivations demonstrated improvements in an overall yield of active enzyme by up to 12‐fold as a result of production under growth‐decoupled conditions. In batch culture, sucrose synthase and UGT71A15 were obtained, respectively, at 115 and 2.30 U/g cell dry weight, corresponding to ∼5 and ∼1% of total intracellular protein. Fed‐batch production gave sucrose synthase in a yield of 2, 300 U/L of culture (830 mg protein/L). Analyzing the isolated glycosyltransferase, we showed that the improvement in the enzyme production was due to the enhancement of both yield (5.3‐fold) and quality (2.3‐fold) of the soluble sucrose synthase. Enzyme preparation from the decoupled production comprised an increased portion (61% compared with 26%) of the active sucrose synthase homotetramer. In summary, therefore, we showed that the expression in growth‐arrested E. coli is promising for recombinant production of plant Leloir glycosyltransferases. Abstract : Nucleotide sugar dependent (Leloir) glycosyltransferases are important catalysts for small molecule glycosylation. Limitation on applicability in glycoside synthesis arises from the fact that these enzymes are difficult to express in standard microbial hosts. Here, the authors show that a synthetic biology‐based strategy of decoupling the enzyme expression from Escherichia coli BL21(DE3) cell growth was effective in enhancing (up to 12‐fold) the individual and combined production of two glycosyltransferases, sucrose synthase and flavonoid glycosyltransferase, as correctly folded and biologically active proteins.